Analysis of the Effect of Project-Based Deep Learning on Diversity in Instilling Creative and Disciplined Character in Students - Qurnia Isna Arahim; Arief Cahyo Utomo (Lembaran Ilmu Kependidikan, 2026)
Background – Developing creative and disciplined character is an essential aspect of 21st-century education. Elementary students require learning approaches that foster critical thinking, creativity, and self-discipline to prepare them for future academic and social challenges. Integrating deep learning with Project-Based Learning (PBL) provides a practical strategy to cultivate these character traits through meaningful, student-centered activities. Purpose – This study aims to describe the implementation of deep learning integrated with Project-Based Learning through a diversity clipping project in fostering creative and disciplined character among third-grade students of SD Muhammadiyah 16 Karangasem. Method/Approach – This qualitative research employed a phenomenological design. Data were collected through interviews with teachers and students, classroom observations during the project, and documentation of students’ work. The study focused on understanding how the learning process influenced students’ creative and disciplined behaviors. Findings – The findings indicate that deep learning through a clipping-based project contributes to the development of students’ creative character, reflected in active participation in group discussions, the ability to generate diverse ideas, flexible thinking, and careful task completion. Students’ disciplinary character is enhanced through adherence to learning rules, time management, and responsibility in completing group tasks. Despite challenges such as limited time for lesson planning and character assessment, the project demonstrates positive potential in supporting character development. Teachers addressed these constraints by collaborating through the KKG forum to improve lesson plans and integrate appropriate character values. Conclusions – The study provides evidence that deep learning integrated with a diversity clipping project can effectively foster both creative and disciplined character in elementary school students. Teacher collaboration and thoughtful lesson planning are key to maximizing the benefits of this learning approach. Novelty/Originality/Value – This research offers valuable insights into combining deep learning and Project-Based Learning to develop students’ character. It serves as a reference for future studies exploring innovative strategies to cultivate creativity and discipline in primary education.